A novel application of lemmatize and thematic analysis to understand protective measures perspectives of patients with chronic respiratory disease during the first outbreak of COVID-19 pandemic: a qualitative study - Palacios-Ceña, Domingo; Peña-Otero, David; Casanova-Macario, Ciro; Cuenca-Zaldivar, Juan Nicolas; Garcia-Bravo, Cristina; Fernandez-de-las-Peñas, Cesar; Díaz-Pérez, David (Frontiers in Public Health, 2024)
Objective: To describe the perspectives of a group of COPD patients during the first outbreak of the COVID-19 pandemic and narrate the emotions and polarity (acceptance-rejection) regarding living with COPD during the pandemic. Design/methods: We used a novel application of lemmatization and thematic analysis of participants' narratives. A study was carried out with eight patients with moderate-severe-very severe COPD during the first outbreak of COVID-19 using purposive sampling. In-depth interviews and field notes from the researchers were used to collect data. A statistical content analysis (lemmatization) of the patients' narratives was performed. Additionally, inductive thematic analysis was used to identify emerging themes. This study was conducted following the guidelines of Consolidated Criteria/Standards for Reporting Qualitative Research. The study was conducted in accordance with the principles articulated in the WMA Declaration of Helsinki. Participants provided verbal informed consent prior to their inclusion as previously described. Results: The average age of our sample was 65 years, and 75% of the patients suffered from moderate COPD, 12.5% from severe COPD, and 12.5% from very severe COPD according to GOLD criteria. The lemmatized and sentiment analysis showed a predominance of positive emotions, and the polarity of the interviews indicated a very slight positive trend towards acceptance of the experience lived during the pandemic. Additionally, three main themes were identified: 1) Confinement and restriction measures, 2) COVID-19 and protective measures, and 3) Clinical care during the first outbreak of the pandemic. Conclusions: Patients experienced confinement with a feeling of security and protection. They strictly respect social distancing. They used masks, but these caused them to feel short of breath and fatigue, especially FFP2 masks. Half of the patients rejected the possibility of being vaccinated. Finally, they were very satisfied with the clinical care they received in the COPD unit of their hospital. Our results show that COPD patients have not experienced a negative impact of the COVID-19 pandemic.